“It’s There, but Not for Us”: Pharmacy Students’ Lived Experiences of Mental Health Support at a South African University - Nqobani M. Dabengwa; Sue F. Burton; Shabnam Shaik (Pharmacy, 2026)
This study explored pharmacy students’ lived experiences of mental health support structures at a University in South Africa. A qualitative phenomenological design was employed, with data collected through semi-structured interviews (n = 20) and document analysis of institutional mental health resources (2020–2024). Thematic analysis revealed five interrelated themes: awareness and visibility of support; barriers to access and utilization; institutional responses to mental health crises; cultural and contextual misalignment; and informal support and coping strategies. Although formal support services were available, students experienced them as fragmented, reactive, and insufficiently integrated into academic life. Barriers to access included long waiting times, stigma, and concerns about confidentiality. Institutional responses to crises were perceived as academically focused, with limited psychological follow-up. Students relied heavily on informal networks, including peers, family, and spirituality. These findings highlight a disconnect between institutional provision and student experience, underscoring the need for more integrated, culturally responsive, and student-centred approaches to mental health support within pharmacy education.